Constraints and Strategies for Inclusive Education in Indonesia at the Primary School Level: A Literature Review - Humayra' Nafisah Mar'atul Latif; Pramesti Pradna Paramita (Da'wa Faculty of Islamic State University Salatiga, 2023)
Inclusive education in Indonesia is designed for all learners, both